2015
DOI: 10.7731/kifse.2015.29.4.049
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Assessment of Combustion Gases from Interior Materials

Abstract: Toxic gases from five types of interior building materials were investigated according to Naval Engineering Standard (NES) 713. The materials were plywood, indoor wall coverings (wood wall plate members and pine wood), reinforced Styrofoam insulation, laminate flooring, and PVC. Specimens were measured using an NES 713 toxicity test apparatus to analyze the hazardous substances in combustion gas from the materials. We used the US Department of Defense standard (MIL-DTL, Military Standard) to calculate the toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…However, according to previous studies, when the toxicity index limit is applied to housing, if the toxicity index is greater than 1.5, the risk of injury or disability from a fire is higher in humans that are exposed to that environment for more than 30 min (Chauhanm et al 2012;Seo and Son 2015). Overall, the toxicity index results demonstrated that the FRCs developed in this study had a low risk for indoor use.…”
Section: Toxicity Index Of the Combustion Gasesmentioning
confidence: 55%
“…However, according to previous studies, when the toxicity index limit is applied to housing, if the toxicity index is greater than 1.5, the risk of injury or disability from a fire is higher in humans that are exposed to that environment for more than 30 min (Chauhanm et al 2012;Seo and Son 2015). Overall, the toxicity index results demonstrated that the FRCs developed in this study had a low risk for indoor use.…”
Section: Toxicity Index Of the Combustion Gasesmentioning
confidence: 55%
“…These ignition times were shorter than the average ignition time of wood and wood-based panels (9 to 50 s), including particle board (PB), high-density fiberboard (HDF), plywood, and laminated flooring (Lee et al 2011). In addition, fire-retardant treated wood-based panels have shown an ignition time of around 65 to 85 s (Seo et al 2015). For wood and wood-based panels, when heat is applied to the object, thermal decomposition progresses step by step as the temperature increases due to the applied heat.…”
Section: Burning Features Of the Wood-fiber Insulation Boardmentioning
confidence: 93%
“…A particular problem is the extensive introduction of various types of artificial materials in buildings, including dwellings, since the 1950s. Different plastic materials with the potential to emit highly toxic gases are present in many interior products and finishes (Seo and Son 2015). Energetic petroleum-based polyurethane foam has largely replaced natural materials in furniture upholstery.…”
Section: Effectiveness Of Measuresmentioning
confidence: 99%